ARTIFICIAL INTELLIGENCE: AN OPPORTUNITY FOR HUMANS AND A THREAT TO INTELLECTUAL STABILIZATION (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the transformation of Artificial Intelligence (AI) technologies in modern society, its economic efficiency, and hidden threats to human cognition. The study highlights evidence-based strategic recommendations to overcome cyber security challenges, the digital divide, and "cognitive laziness" in education, drawing on international experiences